Thermally triggered theranostics for pancreatic cancer therapy. Issue 34 (22nd August 2017) - Malekigorji, Maryam; Alfahad, Mohanad; Kong Thoo Lin, Paul; Jones, Stefanie; Curtis, Anthony; Hoskins, Clare
Abstract : Heat initiated drug release from a hybrid nanoparticle surface after laser irradiation in pancreatic cancer models. Abstract : Hybrid iron oxide–gold nanoparticles (HNPs) show the ability to bind drugs onto their surface with a triggered release at elevated temperatures. The iron oxide core allows for diagnostic imaging whilst heating of the gold shell upon laser irradiation reverses drug binding. This study exploits the reversible binding of novel polyamine based drugs in order to provide a specific and effective method for pancreatic cancer treatment. Here we used a novel bisnaphthalamido (BNIP) based drug series. Our hybrid nanoparticles (50 nm) showed the ability to load drugs onto their surface (3 : 1 : 0.25, drug : Fe : Au). By exploiting the surface-to-drug electrostatic interaction of a range of BNIP agents, heat triggered drug release was achieved. A 12-fold reduction in IC50 after 24 h in vitro and a 5-fold reduction of tumour retardation in vivo compared with free drug in pancreatic models after treatment were achieved with the HNP-formulation and laser irradiation. This heat activated system could provide a key platform for future therapeutic strategies.